A Cluster of Recently Inserted Transposable Elements Associated with siRNAs in Gossypium raimondii. Issue 2 (1st July 2015) - Gong, Lei; Masonbrink, Rick E.; Grover, Corrinne E.; Renny‐Byfield, Simon; Wendel, Jonathan F.
Abstract : Stabilization of transposable element (TE) copy number involves the biosynthesis of short silencing RNAs (siRNAs) and further initialization of siRNA‐mediated TE silencing. To gain insight into the relationship between the biosynthesis of siRNAs and their source TEs, we examined the co‐evolutionary dynamics and expression of these two entities by characterizing the siRNA distribution across the genome of Gossypium raimondii Ulbr. We identified an unusual region at the 3' end of chromosome 1 with significantly enriched siRNA coverage. Analysis of the correlation pattern between uniquely mapped siRNAs and those mapping to multiple regions implicated active biogenesis of siRNAs from these potential young TEs. Furthermore, divergence estimates of TEs within this region confirmed that the majority of TEs are young. Active transcription of the source TEs and their positive correlation with expressed siRNAs indicates that sufficient expression of TEs may be necessary to generate siRNAs and maintain the silenced state of recently transposed TEs.